Baghdadi Serai, Kermanshah: Samples of Iran-Iraq Interactions in the Qajar Period - Isa Hojjat; Efran Heidari (صفه)
The Qajar Period witnessed a period of increased commerce and cultural interactions between Iran and its neighboring countries. As a border town acting as a trans-boundary commercial hub, Kermanshah became home to a group of Jewish immigrants who came from Baghdad and settled in their own quarters. These immigrants developed their specific architecture merging patterns from local architecture with those imported from their former place of residence. The resulting architectural typology is collectively called the Baghdadi Serai. Several samples of this typology remain from the 19th century when this architecture was at its peak. This paper compares architectural features of this typology with other structures built in the same period in Kermanshah. Their architectural elements both show similarities and differences in the entrance, courtyard, colonnades, sash windows, basement, ornament and visual connection with the exterior. This comparative analysis demonstrates how two related architectures are combined in form of a distinct architecture expressing the identity of a specific migrant ethnicity.